Manufacturing of Sustainable Cellulose Date Palm Fiber Reinforced Cementitious Boards in Iraq - Riyad H. Alanbari; Maan S. Hassan; Ali H. Fakhri (Engineering and Technology Journal, 2015)
The present work investigates the suitability of utilizing date palm residues in manufacturing wood-based cementitious boards. It also concerns other environment issues like trying to consume the pollutant carbon dioxides in the boards manufacturing process as an accelerated curing method. Two categories of date palm cellulose fiber cement boards were produced and evaluated, (8% and 5% cellulose fiber content by weight). Comparisons were made between the flexural strengths, stiffness and toughness of the produced boards whichfabricated with conventional and different concentrations of CO2 curing (i.e. 0%, 30%, and 100%). This paper is an attempt to fabricate sustainable products- preferably environmentally friendly- that incorporate agriculture waste in Iraq. Analysis results yielded that higher concentration (100%) has significant effects on the performance of the produced boards, particularly in lower fiber/matrix ratio (5%). Lower CO2 concentration; however, were generally comparable to those obtained at 0% concentration (conventional curing). SEM images confirm the matrix densification effect due to CO2 curing.